Functional Movement Screening Performance and Association With Key Health Markers in Older Adults. Issue 11 (November 2021) - Farrell, Stephen W.; Pavlovic, Andjelka; Barlow, Carolyn E.; Leonard, David; DeFina, Joseph R.; Willis, Benjamin L.; DeFina, Laura F.; Haskell, William L.
Abstract : Abstract: Farrell, SW, Pavlovic, A, Barlow, CE, Leonard, D, DeFina, JR, Willis, BL, DeFina, LF, and Haskell, WL. Functional movement screening performance and association with key health markers in older adults. J Strength Cond Res 35(11): 3021–3027, 2021—We examined Functional Movement Screening (FMS) performance and associations with key health markers among adults aged 55 years or older. Apparently healthy men ( n = 425) and women ( n = 158) completed a preventive medical examination between 2013 and 2018. Subjects were grouped by age and sex to determine mean scores for individual FMS items as well as total FMS score. We examined partial correlations between total FMS score and key health markers. We computed odds ratios (ORs) for having a total FMS score ⩽14. The mean FMS scores for men and women were 11.7 ± 2.8 and 11.9 ± 2.3, respectively. Several differences were found between men who participated in FMS (takers) compared with FMS nontakers, whereas women FMS takers were generally similar to women FMS nontakers. After controlling for age, sex, and smoking, FMS scores were directly associated with physical activity (PA), cardiorespiratory fitness, frequency of resistance training, serum vitamin D, omega-3 index, low-density lipoprotein, and high-density lipoprotein (HDL)-cholesterol, and were inversely associated with body mass index (BMI), waist circumference (WC), blood glucose, HbA1c, and metabolic syndrome ( p ⩽ 0.02 for each). Adjusted OR for scoring ⩽14 was significantly greater for those who were BMI and WC-obese, those with metabolic syndrome, those with low HDL-cholesterol, and those not meeting current PA guidelines. This study provides characteristics and mean values for FMS in a large older population and demonstrates that FMS performance is associated with key health markers. Prospective studies of older adults are needed to determine the utility of FMS in predicting future musculoskeletal injury and other chronic disease–related health outcomes.